The Effect of Brewers' Spent Grain on Markers of Cardiovascular Disease Risk in Healthy Adults: A Randomized Controlled Trial. (7th June 2021) - Combest, Shannon; Warren, Cynthia; Grams, Marley; Wang, Wanyi; Miketinas, Derek; Patterson, Mindy
Abstract: Objectives: The brewing industry generates larges amounts of leftover malted barley and grain adjuncts from beer production called brewers' spent grain (BSG). Due to the high protein and fiber content, upcycling BSG into functional foods has gained recent interest. Observational studies demonstrate fiber-rich whole grains such as barley are associated with cardiovascular disease (CVD) risk reduction. This study evaluated the effect of BSG on blood biomarkers of CVD risk, glucose metabolism, insulin sensitivity, inflammation, body composition, and blood pressure. Methods: A single-blind, randomized, controlled feeding study was conducted in 37 healthy adults (26 ± 4 y; BMI 23 ± 3 kg/m 2 ) comparing consumption of muffins with 10.4 g BSG (n = 19) or 0 g BSG (control; n = 18) daily for 8 weeks. At baseline and week 8 fasting blood was collected for lipids, glucose, insulin, and C-reactive protein, blood pressure was measured using the oscillometric technique, and body composition was assessed using air displacement plethysmography. Participants also recorded 3-day dietary intake, 2-day gastrointestinal symptoms and bowel habits, and daily muffin consumption. Two-way repeated-measures mixed analysis of variance (ANOVA) and Fisher's Least Significant Difference (LSD) tests examined between- and within-group differences. Results: Dietary fiber intake increased in the BSG group (5 g/day; 26%; P = 0.003), but there were no significant effects on blood lipids, glucose metabolism, insulin sensitivity, inflammation, body composition, or blood pressure. Greater reductions of total cholesterol (-3.8 mg/dL), triglycerides (-3.4 mg/dL), and systolic blood pressure (-1.4 mm Hg), maintenance of low-density lipoprotein cholesterol (LDL-C) (0.9 mg/dL), and increases in high-density lipoprotein cholesterol (HDL-C) (2.3 mg/dL) were observed in the BSG group at week 8 but significance was not achieved. Conclusions: Consuming 10.4 g BSG daily for 8 weeks increases dietary fiber intake and is well tolerated when habitually consumed but does not significantly impact blood biomarkers of CVD risk, body composition, or blood pressure in healthy adults. Participant health status, BSG dosage, and study design may be key determinants of outcome measures and should be further evaluated in future studies. Funding Sources: Jennifer Thomas Brown Memorial Nutrition Award and Moore-Khourie Award.